Pengaruh Brand Image dan Hedonic Lifestyle Terhadap Keputusan Pembelian Melalui Emotional Value - Gita Rogayah; RA Nurlinda (Indonesian Journal of Strategic Management, 2023)
The aim of this study is to find out the effect of brand image, hedonic lifestyle, and emotional value on purchase decisions, as well as to know the indirect effect of brand image and hedonic lifestyle on purchase decisions through emotional value. This study is a causal quantitative research and uses a data analysis method Path Analysis. Data collection was carried out by survey with a questionnaire. The population in this study is made up of 165 respondents who have purchased and used Buttonscarves hijab products. The result shows that brand image had a positive effect on emotional value, while hedonic lifestyle had no positive effect on emotional value. Brand image, hedonic lifestyle, and emotional value have a positive effect on purchase decisions. Therefore, brand Image had a positive effect on purchase decisions through emotional value. A hedonic lifestyle had no effect on purchase decisions through emotional value.